Development and In Vitro-In Vivo Evaluation of Extended-release Multiple-unit Pellet System Tablets of Metoprolol Succinate - Reddy, G. Lakshmi Narayana (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To design, develop, and evaluate the metoprolol succinate extended-release (ER) multiple-unit pellet system (MUPS) tablets. Materials and Methods: Metoprolol succinate ER pellets were prepared using Wurster process. The impact of the various concentrations of polymer and plasticizers were studied. Further optimized metoprolol succinate ER pellets were compressed into MUPS tablets and evaluated for various physico-chemical and pharmacokinetic parameters. Results and Discussion: Metoprolol succinate ER MUPS tablets prepared by using 7.5% w/w of ethocel as release retardant and 15% w/w of the plasticizer with respect to the polymer. The release extended for 20 h. Conclusion: Research work indicates that the test formulation was able to extend the delivery of metoprolol in the desired rate.